OX40, PD‐1 and CTLA‐4 are selectively expressed on tumor‐infiltrating T cells in head and neck cancer. Issue 4 (15th April 2016) - Montler, Ryan; Bell, R Bryan; Thalhofer, Colin; Leidner, Rom; Feng, Zipei; Fox, Bernard A; Cheng, Allen C; Bui, Tuan G; Tucker, Christopher; Hoen, Helena; Weinberg, Andrew
Abstract : The tumor microenvironment of squamous cell carcinoma of the head and neck (SCCHN) has been shown to be immune suppressive. Therefore, strategies aimed at overcoming this issue could have a positive therapeutic impact. Hence, we investigated the expression of the known immune‐modulatory proteins OX40, programmed cell death protein 1 (PD‐1) and cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) in SCCHN on different T‐cell subsets of tumor‐infiltrating lymphocytes (TIL) to ascertain whether these proteins could potentially be targeted alone or in combination for future clinical trials. T cells from peripheral blood (PBL) and tumor were analyzed for the expression of OX40, PD‐1 and CTLA‐4 in 29 patients undergoing surgery. These proteins were all expressed significantly higher in T‐cell subsets isolated from tumors compared with PBL of the same patient. OX40 expression was significantly greater in the TIL regulatory T‐cell (Treg) population relative to conventional CD4 and CD8 TIL or the Treg isolated from PBL. PD‐1 expression was increased in all T‐cell subsets relative to PBL. CTLA‐4 was also increased in all TIL subsets relative to blood, and similar to OX40, its highest level of expression was observed in the Treg TIL. The highest frequency of PD‐1, CTLA‐4 and OX40 triple‐positive cells were found in the Treg population isolated from the tumor. We analyzed both human papilloma virus‐positive and ‐negative patients and found similar levels and expression patterns of these two patient populations for all three proteins. These data suggest that there may be therapeutic advantages of targeting these pathways independently or in combination for patients with this disease. Cancer: Vulnerabilities in head and neck tumors: A survey of tumor‐associated immune cells suggests that some head and neck cancers may be vulnerable to potent 'checkpoint inhibitor' drugs. These therapeutic agents work by reactivating dormant host immune cells, which clinical trials have shown to subsequently eradicate various difficult‐to‐treat tumors. Researchers led by Andrew Weinberg at AgonOx, Inc., Portland, in the USA explored whether such drugs might prove effective against squamous cell carcinoma of the head and neck, an often lethal cancer. Their results demonstrated that tumor‐associated immune cells from such patients expressed higher levels of three different cell‐surface proteins targeted by existing checkpoint inhibitors. These proteins were especially abundant on a subset of cells that suppress rather than stimulate the immune response. However, checkpoint inhibitors may act differently on these cells, and the authors hope to explore this in clinical trials.